ANALISI PERSEPSI MAHASISWA TENTANG GOOGLE TRANSLATE (STUDI KASUS DI DEPARTEMEN PENDIDIKAN BAHASA JERMAN UPI) - Anisya Firdha Khairani, - (2020)
Google Translate is a translator machine that can translate various phases of translation with multi-features. However, the results of Google Translate translations are still limited and often sustain errors because there is still a lack of attention to new terms adopted by a language. Accordingly, a study of student perceptions about Google Translate was conducted. This study aims to inquire about the experience and the perception of students of German Language Education Department FPBS UPI in using Google Translate. This study used a qualitative analysis with a descriptive case study method. The subjects are students of German Language Education Department with a representative sample of each population. This study used the form of a questionnaire for the instrument. The result showed: 1) the students' are more often use Google Translate on smartphones because it can translate various forms of text and media such as words, sentences and web pages. All forms of translation and features have been used by students. Also, Google Translate helps them in learning German; 2) the students' considered that the speed and accuracy of Google Translate in translating were good and effective, and they also indicated that they would continue to use Google Translate in the future. The language equivalents in German and Indonesian are not the same which makes the translation result still wrongs, but the tudents work around incorrect translation results by making improvements manually. However, the accuracy of the translation results is good, making it easy to understand. Thus, it can be concluded that students' perception of Google Translate is good. Their experience and perception show that Google Translate is still appropriate to be used as a translation tools. As further research material it is advisable to analyse and compare the translation results of each feature owned by Google Translate.